2021
DOI: 10.1111/jcmm.16896
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps impair regeneration

Abstract: Fibrosis is a major health burden across diseases and organs. To remedy this, we study wound‐induced hair follicle neogenesis (WIHN) as a model of non‐fibrotic healing that recapitulates embryogenesis for de novo hair follicle morphogenesis after wounding. We previously demonstrated that TLR3 promotes WIHN through binding wound‐associated dsRNA, the source of which is still unclear. Here, we find that multiple distinct contexts of high WIHN all show a strong neutrophil signature. Given the correlation between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 77 publications
(180 reference statements)
0
7
0
Order By: Relevance
“…Moreover, since dapagliflozin reduces the anaerobic glycolysis, 36 main metabolism on activated neutrophils, and CD11B expression levels, might suggest a protective role against inflammation response on patients with obesity and HFpEF progression 37 . Moreover, the higher presence of RNase2 and 3 in neutrophils from obese patients, which are involved on extracellular matrix remodelling, 38 might drive to an impaired myocardial regeneration 38,39 . Although further studies are needed, the results of this study contribute to understand the protective dapagliflozin mechanisms underlying HF 40 …”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, since dapagliflozin reduces the anaerobic glycolysis, 36 main metabolism on activated neutrophils, and CD11B expression levels, might suggest a protective role against inflammation response on patients with obesity and HFpEF progression 37 . Moreover, the higher presence of RNase2 and 3 in neutrophils from obese patients, which are involved on extracellular matrix remodelling, 38 might drive to an impaired myocardial regeneration 38,39 . Although further studies are needed, the results of this study contribute to understand the protective dapagliflozin mechanisms underlying HF 40 …”
Section: Discussionmentioning
confidence: 81%
“… 37 Moreover, the higher presence of RNase2 and 3 in neutrophils from obese patients, which are involved on extracellular matrix remodelling, 38 might drive to an impaired myocardial regeneration. 38 , 39 Although further studies are needed, the results of this study contribute to understand the protective dapagliflozin mechanisms underlying HF. 40 …”
Section: Discussionmentioning
confidence: 94%
“…In contrast, type-2 anti-inflammatory macrophages might play an essential role in wound fibrosis by promoting fibrotic fibroblast activation and collagen cross-linking 3 via fibrotic cytokines such as transforming growth factor–beta (TGF-β) 13 and RELMα 14 or chronic phagocytosis activity 4 at a later stage. Although the role of macrophages in pathogen clearance and tissue fibrosis 15 has long been stressed, only recently have the T lymphocytes been more thoroughly investigated. In addition to γδ T cells that induce HF neogenesis through the secretion of fibroblast growth factor 9 (Fgf9) 6 , the adaptive T cells are being explored to gain more understanding of its role in regulating macrophage polarization and, thus, wound regeneration 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The process further integrates M2 macrophages, which express growth factors important for the regulation of the hair cycle and hair growth, such as fibroblast growth factor (FGF)-2 and insulin-like growth factor (IGF)-2 [42]. However, the WHIN process, and thus to some extent general regeneration, appears to be susceptible to inhibition by mature neutrophils because mice deficient in mature neutrophils have higher WIHN [43].…”
Section: Structure and Contents Of The Skin -Multilayer Barriermentioning
confidence: 99%
“…However, NET production is not always accompanied by a positive effect. It has been shown that impaired NET production leads to increased WIHN, indicating that neutrophils may even hinder regeneration in the later course of wound healing [43].…”
Section: Inflammatory Phase -Cell Recruitment and Functionsmentioning
confidence: 99%